Ocular Manifestations in Children with Vernal Keratoconjunctivitis - Matteo Capobianco; Marco Zeppieri; Giuseppe Gagliano; Federico Visalli; Fabiana D’Esposito; Roberta Foti; Ludovica Cannizzaro; Daniele Tognetto; Caterina Gagliano (Children)
Background: Vernal keratoconjunctivitis (VKC) is a chronic, recurrent, and frequently severe allergic ocular condition predominantly impacting children and adolescents in tropical and subtropical areas. It profoundly affects patients’ quality of life owing to its chronic symptoms and possible vision-threatening effects. Notwithstanding progress in comprehending VKC, its ocular symptoms and therapeutic approaches necessitate ongoing assessment. Aims: This review summarizes the main factors to consider when diagnosing, treating, and managing patients with VKC based on the current literature in this field. Methods: This comprehensive review examined peer-reviewed literature from 2010 to 2024 obtained from PubMed. The selection criteria encompassed research addressing the clinical presentation, diagnostic difficulties, and therapy of visual symptoms in pediatric patients with VKC. The publications chosen were those focusing on those that elucidate the pathophysiology, consequences, and innovations in treatment methodologies. Results: The ocular manifestations of VKC are varied and characterized by prominent symptoms such as severe itching, photophobia, lacrimation, and a viscous mucoid discharge. Clinical manifestations range from conjunctival hyperemia and limbal thickening to severe consequences that jeopardize vision, including shield ulcers and keratoconus. Improvements in imaging techniques such as anterior segment optical coherence tomography (AS-OCT) and in vivo confocal microscopy have enhanced diagnostic accuracy. The pharmacological approach has transitioned to steroid-sparing techniques, prioritizing mast cell stabilizers, antihistamines, and immunomodulators such as cyclosporine. Novel therapies, including biologics that target interleukin pathways, demonstrate potential in refractory instances. Nonetheless, access to modern medicines is restricted in resource-limited environments. Conclusions: VKC poses considerable diagnostic and treatment difficulties due to its chronic nature and possible consequences. This review emphasizes the necessity for prompt diagnosis and customized management approaches to avert vision impairment. Despite considerable advancements in comprehending VKC’s etiology and therapy, inequalities in access to sophisticated care highlight the necessity for global activities to guarantee equitable treatment alternatives.